From Theory to Practice: Examining the Curriculum-Industry Gap Through a Digital Marketing Internship in International Education - Eaint Chan Myae (Jurnal Multidisiplin West Science, 2026)
Despite the constant change in the way marketing is conducted in the digital age, there is a lack of alignment between what is taught in university courses and the skills required in the field. Reflection paper which examined a ten-month internship program undertaken at Elite Star, an international education consultancy in Indonesia, to assess the preparedness of the intern in the challenges of the professional career starting in the digital marketing field. The study is based on experiential learning theory and research on the alignment between curriculum and practice, and draws the four following competency domains: content creation; customer relationship management; event marketing; and data-driven decision making. The study compares academic preparation in these four competency domains with the actual practice, based on the on-the-job performance. Results show that the university program had a good grounding in the theory of marketing, but lacked some applied, platform-specific and context-sensitive skills, which were predominantly learned in the workplace. The implications of these findings are significant on the concept of redesigning Business and Management curricula for better preparation of graduates for careers in the evolving landscape of digital marketing.